Pemanfaatan Potensi Lokal untuk Penguatan Karakter Desa melalui Sarana Lingkungan dan Informasi Publik - Tiara Ayu Puspita Sari; Taufik Hidayat; Tantri Wisudawati; Yovia Cindy Aulia; Evelyn Yesania Tarihoran; Tiara Firanti; Sudrajat Sudrajat; Tripani Sartika Joya Siahaan; Tisya Humairoh; Fitri Ramadani (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service activity was carried out in Pangkil Village, Teluk Bintan District, as part of the implementation of the Tri Dharma of Higher Education, particularly in the field of community empowerment. The main issues faced by the community were the lack of environmental orderliness, limited waste management facilities, the absence of an updated village map, the need for seasonal information on marine resources, and the unclear boundaries between hamlets. The objectives of the program were to improve the quality of village administration, strengthen environmental awareness, and provide practical tools for daily activities of local residents. The methods applied included observation, participatory design, direct construction, and documentation studies, with active involvement of community members and local government. The outputs consisted of house number boards, communal trash bins, a participatory village map, a seasonal marine resource calendar, and hamlet boundary markers. The results show positive changes, such as an increase in the spatial identity of the village, better waste management practices, and increased awareness of the maritime seasonal cycle. In general, it can be said that the program has successfully achieved its planned objectives. This success can be seen in the increased environmental orderliness through the arrangement of house numbers, increased public awareness of cleanliness through the use of trash bins, and the availability of more accurate spatial data on the village thanks to participatory mapping. Despite several obstacles, such as limited resources and low community participation at the outset, the program successfully achieved its short-term objectives and provided a foundation for future sustainable development initiatives.